A review of perceived diversity in teams: Does how members perceive their team's composition affect team processes and outcomes?. (7th October 2014) - Shemla, Meir; Meyer, Bertolt; Greer, Lindred; Jehn, Karen A.
Summary: In this paper, we review the growing literature on perceived diversity in teams. We aim to clarify the construct of perceived diversity and organize the findings in this emergent line of research. To do so, we develop a framework integrating research emerging on perceived diversity from across several different research fields. We propose that the nature of perceived diversity and its effects can be best understood by identifying the focal point of the diversity perceptions being studied: perceptions of self‐to‐team dissimilarity, of subgroup splits, and of group heterogeneity. Our review concludes that perceived self‐to‐team dissimilarity and perceived subgroup splits mostly have been linked to negative effects for individuals and groups, whereas perceived group heterogeneity has been shown to exert both positive and negative effects on group outcomes. Our review also draws attention to the problem that research on perceived diversity varies not only in definitions and conceptualizations, but also in the methodological approaches towards operationalizing perceived diversity. We conclude by discussing potential areas for future research. Copyright © 2014 John Wiley & Sons, Ltd.